Analysis on the Impact of Digital Finance on Carbon Emissions under the Background of "Double Carbon" - Liang, Rong (Asia Pacific Economic and Management Review, 2025)
Under the background of frequent global extreme climate problems, achieving the goal of peak carbon dioxide emissions and carbon neutrality has become the main policy to promote the process of carbon emission reduction. At the same time, as a new financial form, digital finance has gradually increased its impact on carbon emissions. Through in-depth analysis of the multiple influence mechanisms between digital finance and carbon emissions, this paper discusses the direct and indirect roles of digital finance in promoting the development of low-carbon economy. However, digital finance also faces many challenges in the process of carbon emission application, such as the lagging digital system of carbon finance market, insufficient innovation of digital products of carbon finance, and insufficient understanding and participation of all parties. Therefore, in order to give full play to the positive role of digital finance in reducing carbon emissions, it is necessary to strengthen the construction of digital system of carbon finance market, speed up the design of digital products of carbon finance and improve the understanding and participation of all parties. This paper has important theoretical and practical significance for understanding and using digital finance to promote the development of low-carbon economy.